Estimation of Emtricitabine in Tablet Dosage Form by RP-HPLC - Kiran Kumar, V.; Appala Raju, N. (Asian Journal of Chemistry, 2010)
A simple, precise, rapid and accurate reverse phase HPLC method in isocratic mode has been developed for the estimation of emtricitabine in tablet dosage form. A Hypersil BDS C18, 250 × 4.6 mm, 5 μm particle size, with mobile phase consisting of acetonitrile and 0.03 M KH2PO4 water (pH adjusted to 3.2 with orthophosphoric acid) in the ratio of 60:40 v/v was used. The flow rate was 0.8 mL/min and the effluents were monitored at 260 nm. The retention time was 3.105 min for emtricitabine. The detector response was linear for emtricitabine 4-48 mcg/mL. The respective linear regression equation being, Y = 35167.413x + 22780.1317 for emtricitabine. The limit of detection (LOD) for emtricitabine was found to be 0.04 μg/mL. The limit of quantification (LOQ) for emtricitabine was 0.12 μg/mL. The percentage assay of emtricitabine was 98/57 %. The method was validated by determining its accuracy, precision and system suitability. The results of the study showed that the proposed RP-HPLC method is simple, rapid, precise and accurate, which is useful for the routine determination of emtricitabine in bulk drug and in its pharmaceutical dosage form.